A Study of Humour in the Workplace and Business from a Singapore Persepctive - Teo, Pebble (2007)
This dissertation is concerned with the use of humour in business or workplace with focus on the Singapore context. Drawing on a conceptual framework for the literature review, we trace the origin and development of humour; examine the effectiveness of humour as a managerial device for improving organizational effectiveness; discuss humour and ambivalence and its impact on power distribution, dissent and division within the workplace; identify cultural differences in humour and explore the use of humour from the Singapore perspective. Data is collated and cross-analysed from the questionnaire participated by 250 individuals from varied industries; partially structured interviews with 15 senior management personnel and a case study of 30 customer service representatives through participant observation at a call centre to address the following research questions. What is the humour quotient of Singaporeans and is humour acceptable in business and the workplace?; does management or senior professionals use or encourage the application of humour in business and the workplace, what are the reasons (if any) and what is their perception on management and employees' use of humour?; and, if humour is used as a survival mechanism, how is it being applied in a controlled and stressful environment such as a call centre? With the proposition that humour has the potential of providing significant insights into management and organizational behavior, this study concludes with strong recommendations for future research on humour studies in the workplace and long term suggestions that will benefit both the management and the workforce in Singapore as well as ease the management's concerns of the paradoxical nature of humour.